Jan Paweł II o świętej przestrzeni pielgrzymowania - Ostrowski, Maciej (Studia Pastoralne, 2006)
Every pilgrimage is a unique religious act happening in the space between a permanent dwelling place and a sanctuary. The author analyses a letter by John Paul II „On pilgrimage to the places related to the history of redemption” published in the context of the Great Jubilee 2000, as well as several other papal documents in which the theology of space is developed. He also refers to the biblical texts of the Old and New Testament. The Son of God accepted a human body, and this took place in a specific geographical space which was charged by God’s very presence. These places are witnesses to the redemptive acts. They are also places where God wishes to bless His people with extraordinary grace. They are sanctuaries, temples consecrated in a ceremonious way, places of apparitions and miracles approved by the Church. For centuries men experience a strong desire to „see God’s face” in a visible dimension. Guided by faith people discover God’s presence in certain places and decide to go on a pilgrimage to experience God’s closeness and receive His grace. The ministry should provide support in people’s trials to get closer to God during pilgrimages by emphasising signs allowing to discover the presence of the Holy One as well as by an adequate catechesis that provides initiation into appropriate contemplation of symbols.